The Study of Optimum Conditions for Chlorella vulgaris by the Response Surface Experimental Design - กสิภาร์ กิตติพล; เวียงแก้ว วัชระ; ศรีสรฉัตร์ ศิริวรรณ; สามารถ ชนาธิป (KKU Science Journal, 2012)
The objective of this study was to investigate the optimum conditions for cultivation of Chlorella vulgaris in a 1-L bioreactor using statistical experimental design. The results were successfully determined by response surface methodology of Box-Behnken and will be used to design the pilot plant bioreactor. Experimental factors effecting the optimum conditions were the cultivation temperature of 25 - 40 °C, the pH of 6 - 8 and the volumetric ratio of carbon dioxide of 1.6 – 7.7%. It was found that the optimum conditions for cultivation were 29.6 °C, pH = 7.26 and the volumetric flow rate of carbon dioxide of 16.18 ml/min or carbon dioxide volumetric ratio of 2.63% giving a specific growth rate of 0.389 day-1.